2006
DOI: 10.2337/dc05-2265
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Care and Pregnancy Outcomes in Women With Type 1 Diabetes

Abstract: OBJECTIVE -The objective of this study was to examine the relationship between prepregnancy care, glycemic control, maternal hypoglycemia, and pregnancy outcomes in women with type 1 diabetes.RESEARCH DESIGN AND METHODS -This was a prospective observational cohort study of women with type 1 diabetes who delivered from 1991 to 2002. Outcome measures were attendance at a clinic for prepregnancy care, maternal HbA 1c (A1C) throughout pregnancy, maternal severe hypoglycemic episodes, macrosomia, preeclampsia, prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
6
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(167 citation statements)
references
References 32 publications
6
152
6
3
Order By: Relevance
“…Clearly, prepregnancy care plays an important role, improving early glycemic control and reducing major malformation and perinatal mortality (29). However, our recent data suggest that even the significant improvements in glycemic control achieved by women attending prepregnancy care are still "not good enough," in that they fail to reduce rates of preeclampsia and macrosomia (24,30). These complications are believed to be related to hyperglycemic excursions during the second and third trimesters (30,31), which are clearly demonstrated in this study.…”
Section: -Estimates Of Glycemic Characteristics For Women With Type 1mentioning
confidence: 63%
See 1 more Smart Citation
“…Clearly, prepregnancy care plays an important role, improving early glycemic control and reducing major malformation and perinatal mortality (29). However, our recent data suggest that even the significant improvements in glycemic control achieved by women attending prepregnancy care are still "not good enough," in that they fail to reduce rates of preeclampsia and macrosomia (24,30). These complications are believed to be related to hyperglycemic excursions during the second and third trimesters (30,31), which are clearly demonstrated in this study.…”
Section: -Estimates Of Glycemic Characteristics For Women With Type 1mentioning
confidence: 63%
“…Women randomized to the CGMS intervention were encouraged to wear the device at 4-to 6-week intervals from the booking visit through to 34 weeks' gestation, since our clinical experience suggests greater discomfort associated with wearing the device in later pregnancy. The prepregnancy and antenatal care at these centers has been recently documented (24).…”
Section: Research Design Andmentioning
confidence: 99%
“…It is possible that the offspring of PGDM mothers with poorer glycaemic control during pregnancy would show abnormalities in glucose tolerance or telomere attrition. However, it should be stressed that PGDM mothers with good glycaemic control still suffer a high rate of fetal morbidity [49], and diabetic populations with good glycaemic control still demonstrate evidence of DNA damage and telomere attrition [18,50]. Second, we cannot exclude the possibility that the offspring of PGDM mothers who declined to participate were different from those who consented with respect to diet, lifestyle, social class and anthropometric measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Tripathi et al [93] showed that diabetic women with preconception care were more likely to have better glycemic control 3 months preconception (OR 1.91, 95% CI 1.10-3.04) and in the first trimester (OR 2.05; 95% CI: 1.39 to 3.03). The study by Temple et al [94] showed that the risk of preterm births decreased in diabetic women receiving prepregnancy care (RR 0.64; 95% CI: 0.47 to 0.88). However, another study by the same author reported no difference in rates of pre-eclampsia (13.1 versus 12.6%) [95] between the women who did and those who did not attend prepregnancy care.…”
Section: Diabetesmentioning
confidence: 99%